2017
DOI: 10.3390/computation5030038
|View full text |Cite
|
Sign up to set email alerts
|

CFD-PBM Approach with Different Inlet Locations for the Gas-Liquid Flow in a Laboratory-Scale Bubble Column with Activated Sludge/Water

Abstract: Abstract:A novel computational fluid dynamics-population balance model (CFD-PBM) for the simulation of gas mixing in activated sludge (i.e., an opaque non-Newtonian liquid) in a bubble column is developed and described to solve the problem of measuring the hydrodynamic behavior of opaque non-Newtonian liquid-gas two-phase flow. We study the effects of the inlet position and liquid-phase properties (water/activated sludge) on various characteristics, such as liquid flow field, gas hold-up, liquid dynamic viscos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…This is attributed to the lower bubble sizes in the low viscosity zones due to reduced coalescence. Wang et al [61] also reported this observation.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…This is attributed to the lower bubble sizes in the low viscosity zones due to reduced coalescence. Wang et al [61] also reported this observation.…”
Section: Resultsmentioning
confidence: 59%
“…Anastasiou et al [4] determined the effective liquid viscosity as a function of the gas flow rate from the mean shear rate. The dynamics related to the bubble rise in CMC and xanthan gum solutions were investigated by Islam et al [60] The hydrodynamics of opaque non-Newtonian liquids in bubble columns was examined by Wang et al [61] Xipeng et al [62] investigated the instantaneous and time-averaged flow fields and velocity distributions in Newtonian and non-Newtonian systems.…”
Section: Introductionmentioning
confidence: 99%